Maharashtra State BoardHSC Commerce 11th
Advertisement Remove all ads

Without expanding determinants, prove that |a1b1c1a2b2c2a3b3c3|=|b1c1a1b2c2a2b3c3a3|=|c1a1b1c2a2b2c3a3b3| - Mathematics and Statistics

Sum

Without expanding determinants, prove that `|("a"_1, "b"_1, "c"_1),("a"_2, "b"_2, "c"_2),("a"_3, "b"_3, "c"_3)| = |("b"_1, "c"_1, "a"_1),("b"_2, "c"_2, "a"_2),("b"_3, "c"_3, "a"_3)| = |("c"_1, "a"_1, "b"_1),("c"_2, "a"_2, "b"_2),("c"_3, "a"_3, "b"_3)|` 

Advertisement Remove all ads

Solution

Let D = `|("a"_1, "b"_1, "c"_1),("a"_2, "b"_2, "c"_2),("a"_3, "b"_3, "c"_3)|`        ...(i)

Let E = `|("b"_1, "c"_1, "a"_1),("b"_2, "c"_2, "a"_2),("b"_3, "c"_3, "a"_3)|`

Applying C1 ↔ C2, we get

E = `-|("c"_1, "b"_1, "a"_1),("c"_2, "b"_2, "a"_2),("c"_3, "b"_3, "a"_3)|` 

Applying C1 ↔ C3, we get

E = `-(- 1) |("a"_1, "b"_1, "c"_1),("a"_2, "b"_2, "c"_2),("a"_3, "b"_3, "c"_3)|`

∴ E = `|("a"_1, "b"_1, "c"_1),("a"_2, "b"_2, "c"_2),("a"_3, "b"_3, "c"_3)|`           ...(ii)

Let F = `|("c"_1, "a"_1, "b"_1),("c"_2, "a"_2, "b"_2),("c"_3, "a"_3, "b"_3)|` 

Applying C1 ↔ C2, we get

F = `-|("a"_1, "c"_1, "b"_1),("a"_2, "c"_2, "b"_2),("a"_3, "c"_3, "b"_3)|`

Applying C2 ↔ C3, we get

F = `-(- 1) |("a"_1, "b"_1, "c"_1),("a"_2, "b"_2, "c"_2),("a"_3, "b"_3, "c"_3)|`

∴ F = `|("a"_1, "b"_1, "c"_1),("a"_2, "b"_2, "c"_2),("a"_3, "b"_3, "c"_3)|`           ...(iii)

From (i), (ii) and (iii), we get

`|("a"_1, "b"_1, "c"_1),("a"_2, "b"_2, "c"_2),("a"_3, "b"_3, "c"_3)| = |("b"_1, "c"_1, "a"_1),("b"_2, "c"_2, "a"_2),("b"_3, "c"_3, "a"_3)| = |("c"_1, "a"_1, "b"_1),("c"_2, "a"_2, "b"_2),("c"_3, "a"_3, "b"_3)|` 

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×